Impact of potential physiological changes due to COVID-19 home confinement on athlete health protection in elite sports: a call for awareness in sports programming - Sarto, F.; Impellizzeri, F. M.; Spörri, J.; Porcelli, S.; Olmo, J.; Requena, B.; Suarez-Arrones, L.; Arundale, A.; Bilsborough, J. C.; Buchheit, M. (Sports Medicine, 2020)
During COVID-19 home confinement, athletes are likely exposed to some level of detraining (i.e. the partial or complete loss of training-induced morphological and physiological adaptations), as a consequence of insufficient and/or inappropriate training stimuli. Such changes may result in impaired performance and increased injury risk if, upon restart, an appropriate sport-specific reconditioning cannot be granted. With this editorial, we aim to recommend extreme caution in sports programming after the COVID-19 emergency